Farmer’s Organization: Lessons Learned from East Java Province, Indonesia - SYAHYUTI, SRI WAHYUNI; SUHAETI, RITA NUR (Journal of Soil and Water Conservation, 2020)
The number of Indonesian cooperatives approximately 192450 units, East Java is known as a barometer and locomotive cooperative movement in Indonesia as one of the co-operative namely Citizens Cooperative of Gresik was ranked 233 in the list of co-operative world in 2013 at the International Cooperative Alliance Global Conference and General assembly (ICA) in Capetown, South Africa. The number of cooperatives in East Java 30,741 units with members 7,248,543. This success spawned many breakthroughs that produced the cooperative movement in East Java, which later became a national program. East Java Province is the center of animal husbandry area where nearly 40% of all cattle in Indonesia in East Java. Currently there were 119 cooperative farms, which consist of 35 cooperative beef cattle, 66 dairy cooperatives, 13 goats and 5 cooperative breeder chicken farm cooperatives. Besides, East Java also has a sizable fishing potential, the current number of cooperatives engaged in the fisheries sector as much as 132 cooperatives, with 113 cooperatives in the fishery business, 15 inland fisheries cooperatives and the cooperative efforts of seaweed. Indonesia is looking for a form of organization of farmers to increase their profits; therefore in the fiscal year 2014 has been carried out a research to assess a lesson learned for the development of cooperatives in various other parts of Indonesia. The study was conducted in 5 core cooperatives in East Java namely: 1). Cooperative Citizens Semen Gresik (KWSG) engaged in providing capital for farming in Gresik Province. 2). Cooperation in the field of rice production in Banyuwangi Province. 3). Cooperation in the field of production of rice in Tulungagung Province. 4). Cooperative fisheries in Malang Province and 5). Cooperative of dairy cow in Tulungagung. The result indicates that the cooperative has had a total of a legal entity, formed through decades of struggle, has diversified units and qualified administrators. The implications of these findings are farmers’organizations should have the legality of the law so as to ensure the clarity of the status of its members in striving to obtain optimal benefits.